The aspects of acquisition of Kannada by 2+ year old children - Sree Devi SV (Journal of All India Institute of Speech and Hearing, 1970)
Studies regarding child's language acqui-sition in Indian languages are scanty. The present study investigated the speech of four Kannada speaking children, two boys and two girls, in the age range of 2 ; 3. 5 to 2 ; 11 . 5. Their socio-economic status and native language were the same. The utterances of the children were recorded in four stages for three children and in three stages for one child with an interval of approximately five weeks between each stage. The elicitation and imitation techniques as well as spontaneous speech were resorted to.